Sea Surface and Atmosphere Conditions for Coherent Reflectometry: On the Impact of Sea Ice and Sea State - Semmling, Maximilian; Moreno Bulla, Mario Andres; Wickert, Jens; Stienne, Georges; Divine, Dmitry; Hoque, Mohammed Mainul; Gerland, Sebastian; Reboul, Serge; Cardellach, Estel (2021)
Coherently reflected GNSS signals are a valuable source for Earth observations. They find application in retrievals of sea surface height with centimetre-level precision as well as for estimation of soil moisture or sea-ice concentration. The application of coherent reflectometry is strongly affected by the transition to the diffuse reflection regime, induced by surface roughness. Also, other factors, like surface penetration, multilayer reflection and atmospheric disturbance, have influence. Our recent investigations are focused on a better understanding of these effects. We review here, on the one hand, a sea-ice reflectometry approach to retrieve sea-ice concentration and sea-ice permittivity considering multilayer reflection. And we discuss, on the other hand, reflections over coastal areas with focus on coherence loss quantified by the signal's Doppler spread under different sea states.